A Meta Analysis of Different Herbs (Leaves, Roots, Stems) Used in Treatment of Cancer Cells - Kumar, Shivam; E., Keshamma; Trivedi, Utkarsh; Janjua, Deepika; Shaw, Pranjal; Kumar, Rohit; Kumar, Roshan; Saha, Purabi (Journal for Research in Applied Sciences and Biotechnology, 2022)
The initial step in the progression of cancer is the deformation of normal cells, which is caused by mutations in the DNA of the cell. This abnormal cell, during the process of it’s asexual reproduction, acquires invasion characteristics and causes alterations in the tissues that are around it, while at the same time ignoring signals linked to the regulation of cell growth that are present in its immediate environment. It would appear that a significant number of the chemical compounds that are created by plants do not play any direct role in the growth of plants. These kinds of molecules are referred to by the phrase "secondary metabolite," which is short for "secondary metabolites." Essential components include alkaloids, terpenoids, flavonoids, pigments, and tannins. Secondary metabolites are responsible for a wide variety of biological effects, including those on hematopoietic cells, lipids, and the cardiovascular system. Other biological effects can also be linked to secondary metabolites.